Documentação de um aplicativo mobile para gerenciamento da entrega de relatórios de projetos universitários - ROCHA, Paula Gisely de Oliveira (2019)
Every passing day we use our smartphones more on tasks that before could only achieve through computers or physical form in commercial or educational establishment. This reality leads us to believe that these devices are increasingly useful and therefore it is important to make the most of their resources. In this context, after conducting a literature review, pursue related work and do field research through interviews and online questionnaires, we realized that the use of such equipment to assist in the progress of scientific research projects or university extension is possible because there are several tasks they are met by school teachers and technicians who have approved projects of this nature. Among them is the fact that you must submit periodic reports on the projects to the bodies of regulation and supervision of the area are the Dean of Extension and Dean of Research and Graduate Studies at the Federal University of Pará. So this work proposed to the documentation for an application on Android platform, able to issue alerts that are intended to remind the engineer responsible for the project, he needs to send certain report within the stipulated time. Such application shall be called Zakar, Hebrew expression that means for us to remember. With the development of this application and subsequent use of it, the deadlines for submission of the aforementioned documents will not be lost, since the application will have the main task to make the coordinator remember that you have to comply with this obligation in a timely manner.